(untitled) (Transport systems and technologies, 2018)
The object of this paper is to analyze the graphics file formats and coding algorithms of digital images. The article begins with a short discussion on the problem of large information sizes of digital images. Then there follows a discussion on the most common coding algorithms and graphical formats. The simulation of four classes of images stored in different graphic formats is presented, in particular, how the coding of the corresponding algorithms influenced the visual and information characteristics of the images. The next paragraph deals with comparison raster graphic format BMP (24-bit) and vector format SVGZ in high quality. Also a similar comparison of images stored in JPEG and SVGZ (low quality) formats was performed and presented. The final paragraph states that the best result showed a binary image translated from bitmap format JPEG into vector format SVGZ. Therefore, judging from the performed simulations, we can conclude that using the SVGZ vector format to convert images from bitmap to vector graphics is appropriate for the first class of images stored in JPEG format, and to the images that contain homogeneous, noise-free colored areas with large areas of repetitive color, such as business graphics, charts, drawings, etc.